2008
DOI: 10.1016/j.scitotenv.2008.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of endocrine-disrupting chemicals in indoor dust

Abstract: Human exposure to indoor dust enriched with endocrine-disrupting chemicals released from numerous indoor sources has been a focus of increasing concern. Longer residence times and elevated contaminant concentrations in the indoor environment may increase chances of exposure to these contaminants by 1000-fold compared to outdoor exposure. To investigate the occurrence of semi-volatile endocrine-disrupting chemicals, including PBDEs (polybrominated diphenyl ethers), PCBs (polychlorinated biphenyls), phthalates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
139
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(163 citation statements)
references
References 59 publications
12
139
4
Order By: Relevance
“…Notably, two studies of PBDE dust levels from California (Hwang et al, 2008;Zota et al, 2008) are absent from Figure 1, because BDE-209 was not analyzed. These two studies have reported some of the highest median concentrations of BDE-47 (2.7 and 2.7 mg/g, respectively) and BDE-99 (4.4 and 3.8 mg/g, respectively) in residential dust.…”
Section: Global Patterns In Pbde Levels Measured In Residential Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, two studies of PBDE dust levels from California (Hwang et al, 2008;Zota et al, 2008) are absent from Figure 1, because BDE-209 was not analyzed. These two studies have reported some of the highest median concentrations of BDE-47 (2.7 and 2.7 mg/g, respectively) and BDE-99 (4.4 and 3.8 mg/g, respectively) in residential dust.…”
Section: Global Patterns In Pbde Levels Measured In Residential Dustmentioning
confidence: 99%
“…In Table 3, we omitted five additional studies (Vorhees et al, 1999;Hwang et al, 2008;Tue et al, 2009;Dirtu and Covaci, 2010), which measured PCBs in residential dust, but did not report individual PCB congener concentrations. Findings from these studies were qualitatively similar to those in Table 3, as the two studies from the United States (Vorhees et al, 1999;Hwang et al, 2008) found relatively high median concentrations of the sum of PCBs (sum of 65 PCBs ¼ 710 ng/g and sum of 54 PCBs ¼ 38.0 ng/g, respectively) compared with studies from Belgium (Roosens et al, 2010a) (sum of 5 PCBs ¼ 17.2 ng/g), Romania (Dirtu and Covaci, 2010) (sum of 8 PCBs ¼ 26.5 ng/g), and Vietnam (Tue et al, 2009) (sum of 34 PCBsB10 ng/g). In Figure 2, we summarize the available data presented in Table 3 and show median dust concentrations reported from each study for any of 5 major PCB congeners (PCBs 105,118,138,153,or 180) that were detected in at least 50% of dust samples.…”
Section: Global Patterns In Pcb Levels Measured In Residential Dustmentioning
confidence: 99%
“…The results raise concerns regarding human exposure to the contaminated soil and dust, and in particular children, because of their long exposure period to these media during play activities and other behavioral characteristics e.g. ingestion of non-food items and regular hand-to-mouth contact (Paustenbach et al, 1997;Lioy et al, 2002;Butte, 2004;Roberts and Ott, 2007;Hwang et al, 2008).…”
Section: Floor Dust and Outdoor Soilmentioning
confidence: 99%
“…A human exposure to indoor dust enriched with endocrine-disrupting chemicals released from numerous indoor sources has been a focus of increasing concern, and longer residence times and elevated contaminant concentrations in the indoor environment may increase chances of exposure to these contaminants by 1000-fold compared to outdoor exposure. For example, in indoor dust samples collected from household vacuum cleaner bags provided by 10 apartments and 1 community hall in Davis, California, USA, bis(2-ethylhexyl) benzene-1,2-dicarboxylate (DEPH) was the most abundant (104-7630 µg ·g −1 ) [144]. DEHP is a manufactured chemical commonly added to plastics and it is known as a rodent carcinogen.…”
Section: Phthalatesmentioning
confidence: 99%